Digital Literacy as Predictors of Students’ Attitude towards Basic Computer Operations in the National Open University of Nigeria - ADEBANJO, Adetayo Adekunle (Ilorin Journal of Education, 2024)
The research is on students’ digital literacy as a predictor of their attitude towards basic computer operations in Lagos centres of the National Open University of Nigeria. The study employed a descriptive survey of correlation. A sample of 238 which comprised 139 females and 99 males from six National Open University of Nigeria study centres in Lagos state, Nigeria was used using purposive sampling techniques from CIT141 learners who participated in the study. The researcher developed and validated computer skill tests and basic computer operations are the main instruments used for data collection. The Pearson product-moment correlation to multiple regression analysis was used to determine the measure of the relationship between independent variables and dependent variables. The results revealed that students’ gender and computer skills had a positive relationship with students’ attitudes toward basic computer operations. The joint effect of students’ gender and computer skills and attitude towards basic computer operations was significant. The relative contribution of students’ computer skills to their attitude toward basic computer operations was significant. Students’ computer skills predicted students’ attitudes toward basic computer operations. It was recommended that students’ computer skills should be taken into consideration when attitude towards basic computer operations is involved.